2009
DOI: 10.1504/ijtm.2009.021526
|View full text |Cite
|
Sign up to set email alerts
|

Information, knowledge and technology management: national information technology policies for sustainable development

Abstract: The paper discusses the relationship among information, knowledge and technology management, with special emphasis on their applications in developing economies and how they relate to sustainable development. It also discusses the role of the national Information Technology (IT) policies in providing enabling environments for Knowledge Management (KM) for sustainable development. Finally, the paper appraises the national IT policies in two African countries (Nigeria and Ethiopia) to further provide insight int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…Biondi et al (2002) focused on the role of European small businesses in achieving environmental sustainability whereas Haigh and Griffiths (2008) studied the impact of IS operational strategies and practices on environmental sustainability. Oukil (2009) explored the key factors for sustainable growth and competitiveness in North African countries and Badamas (2009) considered the information technology policies for sustainable development. Other aspects of sustainable technology management have recently been published by the journal: managing knowledge and technology for sustainable development in Africa (Ahmed, 2009); drivers and barriers, product types and characteristics, process and recovery options, and actors -on firms' waste reduction practices (Wiel et al, 2012); correlation between eco-innovation and competitiveness within some Italian districts (Tessitore et al, 2012); business model blueprints for offshore wind and three suggested generic types of business model innovation (Richter, 2013); collaborative business modelling for systemic and sustainability innovations (Rohrbeck et al, 2013), relationship between information, knowledge and technology management (Tietze et al, 2013); adoption of eco-design practices (Wiggett and Marcelle, 2013) to mention a few.…”
Section: Introductionmentioning
confidence: 99%
“…Biondi et al (2002) focused on the role of European small businesses in achieving environmental sustainability whereas Haigh and Griffiths (2008) studied the impact of IS operational strategies and practices on environmental sustainability. Oukil (2009) explored the key factors for sustainable growth and competitiveness in North African countries and Badamas (2009) considered the information technology policies for sustainable development. Other aspects of sustainable technology management have recently been published by the journal: managing knowledge and technology for sustainable development in Africa (Ahmed, 2009); drivers and barriers, product types and characteristics, process and recovery options, and actors -on firms' waste reduction practices (Wiel et al, 2012); correlation between eco-innovation and competitiveness within some Italian districts (Tessitore et al, 2012); business model blueprints for offshore wind and three suggested generic types of business model innovation (Richter, 2013); collaborative business modelling for systemic and sustainability innovations (Rohrbeck et al, 2013), relationship between information, knowledge and technology management (Tietze et al, 2013); adoption of eco-design practices (Wiggett and Marcelle, 2013) to mention a few.…”
Section: Introductionmentioning
confidence: 99%
“…Successful implementation of large-scale IT initiatives necessitates a transparent relationship between the public and private sectors. It is imperative to establish this relationship’s spectrum of potential outcomes, which spans from cooperation to competition, in the course of the planning phase (Al-Mashari, 2007; Badamas, 2009; El-Gohary et al. , 2006; Frieden, 2005; Lucas et al.…”
Section: Resultsmentioning
confidence: 99%
“…People readiness is among the most important prerequisites of IT plan implementation (Luhan and Novotn a, 2015). All stakeholders and end users should be adequately prepared to implement and utilize the systems (Badamas, 2009;Lam, 2005;Malodia et al, 2021;Pan et al, 2006). Furthermore, in certain nations, individuals converse in two or more languages.…”
Section: Equity and Digital Dividementioning
confidence: 99%
See 2 more Smart Citations